Revisiting the English Textbook Accessibility based on the Universal Design Learning Principles - Asanantha, Emeraldine; Alies Poetri Lintangsari (The Center for Disability Studies and Services Brawijaya University, 2022)
Textbooks based on the teaching and learning process should be relevant to any students including students with disability, there are a lot of textbooks that are not suitable enough to provide accessible material. The goal of this study was to evaluate Universal Design for Learning (UDL) concepts in 2 online modules on UDL that were taught over one semester alongside English as a Foreign Language (EFL) lectures. The module is divided into 10 chapters that each discuss one of five categories of exploratory texts. To clarify the ULD concepts used in the curriculum, this research applied Textbook analysis using the Center for Applied Special Technology (CAST 2018) design framework. The results demonstrate that more ULD concepts, which notably provide multiple means of engagement, representation, and action & expression, can be used to provide better accommodation for blind students to support inclusion in educational materials. In addition, a strong desire to use the UDL concepts in their future teaching is encouraged through university modules. There is a discussion of restrictions and repercussions.